Moisture-proof and corrosion-resistant plastic floor and preparation process thereof

CN123004031APending Publication Date: 2026-10-30CHANGZHOU ZHONGLONG WOOD IND CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611311140.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-27
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

但普通聚丙烯塑料地板自身阻隔能力有限,在潮湿、高盐雾及弱酸弱碱环境下,水分子与腐蚀介质易逐步渗透至材料内部,引发基体老化降解、性能持续衰减,难以满足地下空间、沿海建筑等特殊场景的长期服役需求

Benefits of technology

1、本发明通过核壳结构多功能微胶囊与疏水改性纸纤维的协同配合,构建了“被动阻隔、界面封堵、主动修复”三重递进式防潮耐腐蚀防护体系,大幅提升材料的长效耐蚀防潮性能。一方面,由改性锂渣与聚磷酰胺接枝多面体低聚倍半硅氧烷复合形成的微胶囊刚性外壳,兼具片状硅铝结构的迷宫效应与三维硅氧网络的致密化作用,可显著延长水分子、氯离子等腐蚀介质的扩散路径;经硅烷改性的壳层整体具有强疏水性,可从热力学上抑制水相润湿与极性介质渗透,降低材料吸水率。另一方面,通过硅烷疏水改性与马来酸酐接枝聚丙烯的增容作用,同步消除了纤维-基体、微胶囊-基体两处关键界面的结合缺陷,避免界面缝隙成为介质渗透的快捷通道,保障了整体防护体系的连续性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure REF-OBJ-1787810459557-000001
    Figure REF-OBJ-1787810459557-000001
Patent Text Reader

Abstract

The application discloses a kind of damp-proof corrosion-resistant plastic floor and preparation process thereof, it is related to plastic floor technical field, the present application is first with modified lithium residue, polyphosphamide grafting POSS is composite shell, encapsulates isophorone diisocyanate to prepare multifunctional microcapsule, then it is with hydrophobic modified paper fiber, polypropylene matrix etc. Melt blending, hot-pressing molding is obtained finished product.The present application constructs triple protection system, realizes abrasion resistance and efficiency and mechanical enhancement simultaneously, significantly improves the damp-proof corrosion-resistant performance and long-term service stability of floor.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of plastic flooring technology, specifically to a moisture-proof and corrosion-resistant plastic floor and its preparation process. Background Technology

[0002] With the development of the building decoration industry, polypropylene-based plastic flooring is increasingly widely used in various civil and industrial buildings due to its excellent processing performance, low cost, and strong recyclability. However, ordinary polypropylene plastic flooring has limited barrier properties. In humid, high-salt-spray, and weakly acidic or alkaline environments, water molecules and corrosive media can easily penetrate into the material, causing matrix aging and degradation, and continuous performance decline. This makes it difficult to meet the long-term service requirements of special scenarios such as underground spaces and coastal buildings.

[0003] Reinforcing with natural fibers is the mainstream approach to improve the mechanical properties of flooring and reduce raw material costs. However, the surface of natural fibers is rich in hydroxyl groups, making them highly hydrophilic. Upon absorbing water, they easily expand in volume, leading to fiber-matrix interface separation. This not only degrades the dimensional stability and mechanical properties of the material but also creates rapid channels for media penetration, further exacerbating corrosion and damage. This has become a core bottleneck restricting its widespread application. Existing microencapsulation modification technologies often suffer from insufficient shell density and limited functionality, making it difficult to simultaneously achieve barrier protection, self-repair of damage, and enhanced wear resistance. Furthermore, most rely on expensive functional fillers, lacking low-cost, multi-functional modification solutions that also consider the high-value utilization of large quantities of solid waste. Summary of the Invention

[0004] The purpose of this invention is to provide a moisture-proof and corrosion-resistant plastic flooring and its preparation process, so as to solve the problems raised in the prior art.

[0005] To achieve the above objectives, the present invention provides the following technical solution: A process for preparing a moisture-proof and corrosion-resistant plastic floor includes the following steps: S1: Isophorone diisocyanate, divinylbenzene, and photoinitiator 369 are mixed evenly and ultrasonically dispersed to obtain an oil phase; S2: Add modified lithium slag and polyphosphoramide-grafted POSS to deionized water and stir evenly to obtain an aqueous phase; S3: Add the oil phase to the aqueous phase and stir until homogeneous to obtain a Pickering emulsion; irradiate the Pickering emulsion under ultraviolet light for 40-60 min, filter, wash, and dry to obtain multifunctional microcapsules; S4: Polypropylene, maleic anhydride-grafted polypropylene, hydrophobically modified paper fiber, multifunctional microcapsules, and compound antioxidants are mixed evenly, melt-blended, extruded and granulated, hot-pressed, cooled and demolded to obtain moisture-proof and corrosion-resistant plastic flooring.

[0006] Furthermore, in the preparation of the oil phase, the mass ratio of isophorone diisocyanate, divinylbenzene, and photoinitiator 369 is 1:1:0.03; in the preparation of the aqueous phase, the mass ratio of modified lithium slag and polyphosphoramide-grafted POSS is (2-2.5):1; and in the preparation of the Pickering emulsion, the mass ratio of the oil phase to the aqueous phase is 1:(4-6).

[0007] Furthermore, in the preparation process of the moisture-proof and corrosion-resistant plastic flooring, the proportions of each component by mass parts include: 60-75 parts of polypropylene, 3-5 parts of maleic anhydride-grafted polypropylene, 10-20 parts of hydrophobic modified paper fiber, 8-18 parts of multifunctional microcapsules, and 0.3-0.8 parts of compound antioxidant.

[0008] Furthermore, the method for preparing the modified lithium slag includes the following steps: adding lithium slag to deionized water, heating to 60-65℃ and stirring for 30-35 minutes to prepare a 6-7 wt% lithium slag suspension; mixing γ-methacryloyloxypropyltrimethoxysilane and anhydrous ethanol at a mass ratio of 1:60, adding the mixture to the lithium slag suspension, heating to 80-85℃ and stirring for 10-15 minutes, filtering, and vacuum drying to obtain silane-modified lithium slag.

[0009] Furthermore, the lithium slag is an industrial waste residue produced from lithium extraction from spodumene or lepidolite, and its main components are silicon dioxide and aluminum oxide. Furthermore, in the preparation process of the silane-modified lithium slag, the amount of γ-methacryloxypropyltrimethoxysilane added is 4-6% of the mass of the lithium slag.

[0010] Furthermore, the preparation method of the polyphosphoramide grafted POSS includes the following steps: γ-aminopropyltriethoxysilane and methanol are mixed evenly at a volume ratio of 1:8 and added to a reaction vessel, concentrated hydrochloric acid is added, the mixture is stirred at room temperature for 160-170 h, filtered, and the filter cake is washed with methanol to obtain octaaminopropyl polyhedral oligomeric silsesquioxane hydrochloride. Mix octaaminopropyl polyhedral oligomeric silsesquioxane hydrochloride, triethylamine, and anhydrous ethanol evenly, heat to 60-65℃ and stir for 2.5-3.5 h, add polyphosphoric acid, heat to 90-95℃ and reflux for 5.5-6.5 h, filter, collect the precipitate, wash the precipitate with ethanol, and vacuum dry to obtain polyphosphoramide grafted POSS.

[0011] Furthermore, in the preparation of the octaaminopropyl polyhedral oligomeric silsesquioxane hydrochloride, the volume ratio of γ-aminopropyltriethoxysilane to concentrated hydrochloric acid is 10:3; in the preparation of polyphosphoramide-grafted POSS, the mass ratio of octaaminopropyl polyhedral oligomeric silsesquioxane hydrochloride, triethylamine, and polyphosphoric acid is 11.6:12.6:10.2.

[0012] Furthermore, the preparation method of the hydrophobic modified paper fiber includes the following steps: adding bleached sulfate hardwood paper fiber to deionized water, stirring evenly to prepare a 2-3 wt% paper fiber suspension; mixing γ-methacryloyloxypropyltrimethoxysilane and anhydrous ethanol at a mass ratio of 1:10 evenly, adding the mixture to the fiber suspension, heating to 70-80℃ and stirring for 1.5-2 hours, filtering, washing with deionized water until neutral, and vacuum drying to obtain the hydrophobic modified paper fiber.

[0013] Furthermore, in the preparation process of the hydrophobic modified paper fiber, the amount of γ-methacryloyloxypropyltrimethoxysilane added is 3-5% of the oven-dry weight of the paper fiber.

[0014] Furthermore, during the melt blending process, the temperature of the feeding section is 160-170℃, the temperature of the melting section is 180-190℃, the temperature of the die head section is 190-200℃, and the screw speed is 200-300 r / min.

[0015] Furthermore, the hot pressing molding parameters are as follows: temperature is 180-190℃, pre-pressing pressure is 0.5MPa, pre-pressing time is 2-2.5min, working pressure is 15MPa, holding time is 12-18min, and demolding is performed 2-3min after holding time.

[0016] Furthermore, the compound antioxidant is obtained by compounding antioxidant 1010 and antioxidant 168 in a mass ratio of 3:1.

[0017] Compared with the prior art, the beneficial effects of the present invention are: 1. This invention constructs a triple-progressive moisture-proof and corrosion-resistant protection system—"passive barrier, interface sealing, and active repair"—through the synergistic effect of core-shell structured multifunctional microcapsules and hydrophobically modified paper fibers, significantly improving the long-term corrosion and moisture resistance of the material. On one hand, the rigid outer shell of the microcapsules, formed by the composite of modified lithium slag and polyphosphoramide-grafted polyhedral oligomeric silsesquioxane, combines the labyrinth effect of a sheet-like silicon-aluminum structure with the densification effect of a three-dimensional silicon-oxygen network, significantly extending the diffusion path of corrosive media such as water molecules and chloride ions. The silane-modified shell layer as a whole possesses strong hydrophobicity, which thermodynamically inhibits aqueous wetting and polar medium penetration, reducing the material's water absorption rate. On the other hand, through the hydrophobic modification of silane and the compatibilizing effect of maleic anhydride-grafted polypropylene, the bonding defects at the two key interfaces—fiber-matrix and microcapsule-matrix—are simultaneously eliminated, preventing interface gaps from becoming rapid channels for medium penetration and ensuring the continuity of the overall protection system.

[0018] 2. The multifunctional microcapsules of this invention can achieve synergistic gains in wear resistance and corrosion resistance. The rigid shell of the microcapsules is uniformly dispersed in the matrix as a hard reinforcing phase, which can improve the surface hardness of the material and resist ploughing damage during friction. When the microcapsules rupture due to friction, the released isophorone diisocyanate can form a continuous boundary lubricating film at the friction interface, effectively reducing the coefficient of friction and wear, thus extending the wear-resistant service life of the floor and reducing corrosion intrusion sites such as surface wear pits and microcracks. This reduces the risk of media penetration from the source and further enhances the long-term corrosion resistance of the material.

[0019] 3. This invention uses hydrophobically modified paper fibers as the reinforcing phase, which improves mechanical properties at low cost while solving the industry pain points of traditional natural fiber reinforcing materials being prone to water absorption, swelling, and performance degradation. The hydrophilicity of the silane-modified paper fibers is significantly reduced, which can avoid volume expansion and interfacial delamination caused by fiber water absorption; at the same time, the active groups introduced on the fiber surface can react with the compatibilizer to form a strong interfacial bond between the fiber and the polypropylene matrix, giving full play to the load-bearing and reinforcing role of the fiber and effectively improving the dimensional stability and deformation resistance of the flooring. Detailed Implementation

[0020] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0021] In the following embodiments, the method for preparing the modified lithium slag includes the following steps: adding lithium slag to deionized water, heating to 60°C and stirring for 30 min to prepare a 6 wt% lithium slag suspension; mixing γ-methacryloyloxypropyltrimethoxysilane and anhydrous ethanol at a mass ratio of 1:60, adding the mixture to the lithium slag suspension, heating to 80°C and stirring for 10 min, filtering, and vacuum drying to obtain silane-modified lithium slag.

[0022] In the preparation of the silane-modified lithium slag, the amount of γ-methacryloyloxypropyltrimethoxysilane added is 5% of the mass of the lithium slag.

[0023] The preparation method of polyphosphoramide grafted POSS includes the following steps: γ-aminopropyltriethoxysilane and methanol are mixed evenly at a volume ratio of 1:8 and added to a reaction vessel. Concentrated hydrochloric acid is added, and the mixture is stirred at room temperature for 160 h. The mixture is filtered, and the filter cake is washed with methanol to obtain octaaminopropyl polyhedral oligomeric silsesquioxane hydrochloride. Eight-aminopropyl polyhedral oligomeric silsesquioxane hydrochloride, triethylamine, and anhydrous ethanol were mixed evenly, heated to 60°C and stirred for 3 hours, polyphosphoric acid was added, and the mixture was heated to 90°C and refluxed for 6 hours. The mixture was filtered, the precipitate was collected, washed with ethanol, and dried under vacuum to obtain polyphosphoramide-grafted POSS.

[0024] In the preparation of the octaaminopropyl polyhedral oligomeric silsesquioxane hydrochloride, the volume ratio of γ-aminopropyltriethoxysilane to concentrated hydrochloric acid is 10:3; in the preparation of polyphosphoramide-grafted POSS, the mass ratio of octaaminopropyl polyhedral oligomeric silsesquioxane hydrochloride, triethylamine, and polyphosphoric acid is 11.6:12.6:10.2.

[0025] The preparation method of hydrophobic modified paper fiber includes the following steps: bleached sulfate hardwood paper fiber is added to deionized water and stirred evenly to prepare a 2wt% paper fiber suspension; γ-methacryloyloxypropyltrimethoxysilane and anhydrous ethanol are mixed evenly at a mass ratio of 1:10 and added to the fiber suspension, heated to 70℃ and stirred for 1.5h, filtered, washed with deionized water until neutral, and vacuum dried to obtain hydrophobic modified paper fiber.

[0026] In the preparation of the hydrophobic modified paper fiber, the amount of γ-methacryloyloxypropyltrimethoxysilane added is 4% of the oven-dry weight of the paper fiber.

[0027] Example 1: A preparation process for a moisture-proof and corrosion-resistant plastic floor, comprising the following steps: S1: Mix 1 part isophorone diisocyanate, 1 part divinylbenzene, and 0.03 parts photoinitiator 369 evenly, and disperse by ultrasonication to obtain an oil phase; S2: Add 2 parts of modified lithium slag and 1 part of polyphosphoramide-grafted POSS to deionized water and stir evenly to obtain an aqueous phase; S3: Add 1 part of oil phase to 5 parts of aqueous phase and stir evenly to obtain Pickering emulsion; place the Pickering emulsion under ultraviolet light for 50 min, filter, wash, and dry to obtain multifunctional microcapsules; S4: Mix 68.5 parts polypropylene, 4 parts maleic anhydride-grafted polypropylene, 15 parts hydrophobic modified paper fiber, 12 parts multifunctional microcapsules, and 0.5 parts compound antioxidant evenly, melt blend, extrude granulate, hot press, cool and demold to obtain moisture-proof and corrosion-resistant plastic flooring.

[0028] In the preparation of the oil phase, the mass ratio of isophorone diisocyanate, divinylbenzene, and photoinitiator 369 is 1:1:0.03. In the preparation of the aqueous phase, the mass ratio of modified lithium slag to polyphosphoramide-grafted POSS is 2:1. In the preparation of Pickering emulsion, the mass ratio of the oil phase to the aqueous phase is 1:5.

[0029] Example 2: A preparation process for a moisture-proof and corrosion-resistant plastic floor, comprising the following steps: S1: Mix 1 part isophorone diisocyanate, 1 part divinylbenzene, and 0.03 parts photoinitiator 369 evenly, and disperse by ultrasonication to obtain an oil phase; S2: Add 2 parts of modified lithium slag and 1 part of polyphosphoramide-grafted POSS to deionized water and stir evenly to obtain an aqueous phase; S3: Add 1 part of oil phase to 5 parts of aqueous phase and stir evenly to obtain Pickering emulsion; place the Pickering emulsion under ultraviolet light for 50 min, filter, wash, and dry to obtain multifunctional microcapsules; S4: Mix 68.5 parts polypropylene, 4 parts maleic anhydride-grafted polypropylene, 12 parts hydrophobic modified paper fiber, 15 parts multifunctional microcapsules, and 0.5 parts compound antioxidant evenly, melt blend, extrude granulate, hot press, cool and demold to obtain moisture-proof and corrosion-resistant plastic flooring.

[0030] In the preparation of the oil phase, the mass ratio of isophorone diisocyanate, divinylbenzene, and photoinitiator 369 is 1:1:0.03. In the preparation of the aqueous phase, the mass ratio of modified lithium slag to polyphosphoramide-grafted POSS is 2:1. In the preparation of Pickering emulsion, the mass ratio of the oil phase to the aqueous phase is 1:5.

[0031] Example 3: A preparation process for a moisture-proof and corrosion-resistant plastic floor, comprising the following steps: S1: Mix 1 part isophorone diisocyanate, 1 part divinylbenzene, and 0.03 parts photoinitiator 369 evenly, and disperse by ultrasonication to obtain an oil phase; S2: Add 2 parts of modified lithium slag and 1 part of polyphosphoramide-grafted POSS to deionized water and stir evenly to obtain an aqueous phase; S3: Add 1 part of oil phase to 5 parts of aqueous phase and stir evenly to obtain Pickering emulsion; place the Pickering emulsion under ultraviolet light for 50 min, filter, wash, and dry to obtain multifunctional microcapsules; S4: Mix 67.5 parts polypropylene, 4 parts maleic anhydride-grafted polypropylene, 20 parts hydrophobic modified paper fiber, 8 parts multifunctional microcapsules, and 0.5 parts compound antioxidant evenly, melt blend, extrude granulate, hot press, cool and demold to obtain moisture-proof and corrosion-resistant plastic flooring.

[0032] In the preparation of the oil phase, the mass ratio of isophorone diisocyanate, divinylbenzene, and photoinitiator 369 is 1:1:0.03. In the preparation of the aqueous phase, the mass ratio of modified lithium slag to polyphosphoramide-grafted POSS is 2:1. In the preparation of Pickering emulsion, the mass ratio of the oil phase to the aqueous phase is 1:5.

[0033] Comparative Example 1: A preparation process for a moisture-proof and corrosion-resistant plastic floor, comprising the following steps: S1: Add bleached sulfate hardwood paper fibers to deionized water, stir evenly, prepare a 2wt% paper fiber suspension, filter, vacuum dry, and obtain unmodified virgin paper fibers; S2: Mix 80.5 parts polypropylene, 4 parts maleic anhydride-grafted polypropylene, 15 parts unmodified virgin paper fiber, and 0.5 parts compounded antioxidant evenly, melt blend, extrude granulate, hot press, cool and demold to obtain moisture-proof and corrosion-resistant plastic flooring.

[0034] Comparative Example 2: A preparation process for a moisture-proof and corrosion-resistant plastic flooring, comprising the following steps: S1: 80.5 parts of polypropylene, 4 parts of maleic anhydride-grafted polypropylene, 15 parts of hydrophobic modified paper fiber, and 0.5 parts of compound antioxidant are mixed evenly, melt-blended, extruded and granulated, hot-pressed, cooled and demolded to obtain a moisture-proof and corrosion-resistant plastic flooring.

[0035] Comparative Example 3: A preparation process for a moisture-proof and corrosion-resistant plastic floor, comprising the following steps: S1: Mixing 1 part isophorone diisocyanate, 1 part divinylbenzene, and 0.03 parts photoinitiator 369 evenly and dispersing by ultrasonication to obtain an oil phase; S2: Add 3 parts of modified lithium slag to deionized water and stir evenly to obtain an aqueous phase; S3: Add 1 part of oil phase to 5 parts of aqueous phase and stir evenly to obtain Pickering emulsion; place the Pickering emulsion under ultraviolet light for 50 min, filter, wash, and dry to obtain multifunctional microcapsules; S4: Mix 68.5 parts polypropylene, 4 parts maleic anhydride-grafted polypropylene, 15 parts hydrophobic modified paper fiber, 12 parts multifunctional microcapsules, and 0.5 parts compound antioxidant evenly, melt blend, extrude granulate, hot press, cool and demold to obtain moisture-proof and corrosion-resistant plastic flooring.

[0036] In the preparation of the oil phase, the mass ratio of isophorone diisocyanate, divinylbenzene, and photoinitiator 369 is 1:1:0.03. In the preparation of the aqueous phase, the mass ratio of modified lithium slag to polyphosphoramide-grafted POSS is 2:1. In the preparation of Pickering emulsion, the mass ratio of the oil phase to the aqueous phase is 1:5.

[0037] Comparative Example 4: A preparation process for a moisture-proof and corrosion-resistant plastic floor, comprising the following steps: S1: Mixing 1 part divinylbenzene and 0.03 parts photoinitiator 369 evenly and ultrasonically dispersing to obtain an oil phase; S2: Add 2 parts of modified lithium slag and 1 part of polyphosphoramide-grafted POSS to deionized water and stir evenly to obtain an aqueous phase; S3: Add 1 part of oil phase to 5 parts of aqueous phase and stir evenly to obtain Pickering emulsion; place the Pickering emulsion under ultraviolet light for 50 min, filter, wash, and dry to obtain multifunctional microcapsules; S4: Mix 68.5 parts polypropylene, 4 parts maleic anhydride-grafted polypropylene, 15 parts hydrophobic modified paper fiber, 12 parts multifunctional microcapsules, and 0.5 parts compound antioxidant evenly, melt blend, extrude granulate, hot press, cool and demold to obtain moisture-proof and corrosion-resistant plastic flooring.

[0038] The remaining steps are the same as in Example 1.

[0039] Performance testing: Water absorption and dimensional stability test: The sample was immersed in deionized water at 25℃ for 168h. The changes in mass and size before and after the test were recorded, and the water absorption rate and dimensional change rate were calculated. Static water contact angle test: The static water contact angle of the sample surface is measured using a contact angle measuring instrument; Corrosion resistance test: The sample was immersed in 3.5wt% NaCl solution for 480h, and the bending strength before and after immersion was tested. The strength retention rate was calculated. Wear resistance test: A high-speed friction and wear tester was used with zirconia ceramic balls as the wear object to test the friction coefficient and wear rate under a fixed load of 10N and 200r / min. Mechanical property testing: Bending properties are tested according to ASTM D790, and tensile properties are tested according to ASTM D638.

[0040] The performance test results are shown in Table 1.

[0041] Table 1. Performance Test Data of Moisture-proof and Corrosion-resistant Plastic Flooring

[0042] Conclusion: The moisture-proof and corrosion-resistant plastic flooring prepared by this invention has low water absorption, excellent hydrophobic corrosion resistance and wear resistance, and good mechanical strength and dimensional stability. It can meet the long-term use requirements in humid and corrosive environments and has outstanding application value.

[0043] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, it is intended that all variations falling within the meaning and scope of equivalents of the claims be included within the present invention.

Claims

1. A manufacturing process for moisture-proof and corrosion-resistant plastic flooring, characterized in that: Includes the following steps: S1: Isophorone diisocyanate, divinylbenzene, and photoinitiator 369 are mixed evenly and ultrasonically dispersed to obtain the oil phase; S2: Add modified lithium slag and polyphosphoramide-grafted POSS to deionized water and stir evenly to obtain an aqueous phase; S3: Add the oil phase to the aqueous phase and stir until homogeneous to obtain a Pickering emulsion; expose the Pickering emulsion to ultraviolet light, filter, wash, and dry to obtain multifunctional microcapsules; S4: Polypropylene, maleic anhydride-grafted polypropylene, hydrophobically modified paper fiber, multifunctional microcapsules, and compound antioxidants are mixed evenly, melt-blended, extruded and granulated, hot-pressed, cooled and demolded to obtain moisture-proof and corrosion-resistant plastic flooring.

2. The preparation process of a moisture-proof and corrosion-resistant plastic flooring according to claim 1, characterized in that: In the preparation of the oil phase, the mass ratio of isophorone diisocyanate, divinylbenzene, and photoinitiator 369 is 1:1:0.03; in the preparation of the aqueous phase, the mass ratio of modified lithium slag and polyphosphoramide grafted POSS is (2-2.5):1; in the preparation of the Pickering emulsion, the mass ratio of the oil phase to the aqueous phase is 1:(4-6).

3. The preparation process of a moisture-proof and corrosion-resistant plastic flooring according to claim 1, characterized in that: In the preparation process of moisture-proof and corrosion-resistant plastic flooring, the proportions of each component by mass are as follows: 60-75 parts polypropylene, 3-5 parts maleic anhydride-grafted polypropylene, 10-20 parts hydrophobically modified paper fiber, 8-18 parts multifunctional microcapsules, and 0.3-0.8 parts compound antioxidant.

4. The preparation process of a moisture-proof and corrosion-resistant plastic flooring according to claim 1, characterized in that: The method for preparing the modified lithium slag includes the following steps: adding lithium slag to deionized water, heating to 60-65℃ and stirring for 30-35 minutes to prepare a 6-7 wt% lithium slag suspension; mixing γ-methacryloyloxypropyltrimethoxysilane and anhydrous ethanol at a mass ratio of 1:60, adding the mixture to the lithium slag suspension, heating to 80-85℃ and stirring for 10-15 minutes, filtering, and vacuum drying to obtain silane-modified lithium slag.

5. The preparation process of a moisture-proof and corrosion-resistant plastic flooring according to claim 4, characterized in that: In the preparation of silane-modified lithium slag, the amount of γ-methacryloxypropyltrimethoxysilane added is 4-6% of the mass of the lithium slag.

6. The manufacturing process of a moisture-proof and corrosion-resistant plastic flooring according to claim 1, characterized in that: The preparation method of the polyphosphoramide grafted POSS includes the following steps: γ-aminopropyltriethoxysilane and methanol are mixed evenly at a volume ratio of 1:8 and added to a reaction vessel. Concentrated hydrochloric acid is added and stirred at room temperature for 160-170 h. The mixture is filtered and the filter cake is washed with methanol to obtain octaaminopropyl polyhedral oligomeric silsesquioxane hydrochloride. Mix octaaminopropyl polyhedral oligomeric silsesquioxane hydrochloride, triethylamine, and anhydrous ethanol evenly, heat to 60-65℃ and stir for 2.5-3.5 h, add polyphosphoric acid, heat to 90-95℃ and reflux for 5.5-6.5 h, filter, collect the precipitate, wash the precipitate with ethanol, and vacuum dry to obtain polyphosphoramide grafted POSS.

7. The preparation process of a moisture-proof and corrosion-resistant plastic flooring according to claim 6, characterized in that: In the preparation of octaaminopropyl polyhedral oligomeric silsesquioxane hydrochloride, the volume ratio of γ-aminopropyltriethoxysilane to concentrated hydrochloric acid is 10:3; in the preparation of polyphosphoramide-grafted POSS, the mass ratio of octaaminopropyl polyhedral oligomeric silsesquioxane hydrochloride, triethylamine, and polyphosphoric acid is 11.6:12.6:10.

2.

8. The manufacturing process of a moisture-proof and corrosion-resistant plastic flooring according to claim 1, characterized in that: The method for preparing the hydrophobic modified paper fiber includes the following steps: adding bleached sulfate hardwood paper fiber to deionized water, stirring evenly to prepare a 2-3 wt% paper fiber suspension; mixing γ-methacryloyloxypropyltrimethoxysilane and anhydrous ethanol at a mass ratio of 1:10 evenly, adding the mixture to the fiber suspension, heating to 70-80℃ and stirring for 1.5-2 hours, filtering, washing with deionized water until neutral, and vacuum drying to obtain the hydrophobic modified paper fiber.

9. The manufacturing process of a moisture-proof and corrosion-resistant plastic flooring according to claim 8, characterized in that: In the preparation of hydrophobically modified paper fibers, the amount of γ-methacryloyloxypropyltrimethoxysilane added is 3-5% of the oven-dry weight of the paper fibers.

10. A moisture-proof and corrosion-resistant plastic floor prepared according to any one of claims 1-9.